Comparing linear and cyclic synthetic homopolypeptides: Synthesis and molecular characterization. Issue 3 (24th October 2014) - Politakos, Nikolaos; Liontos, George; Kortaberria, Galder; Messman, Jamie M.; Calvo, Javier; Moya, Sergio E.; Mays, Jimmy W.; Avgeropoulos, Apostolos
ABSTRACT The synthesis and molecular characterization of a linear and a cyclic homopolypeptide of protected l‐tyrosine are reported. In this work, the successful synthesis of polypeptides exhibiting the desired linear and cyclic structures through various characterization methods such as high temperature gel permeation chromatography, Fourier transform infrared spectroscopy, proton and carbon nuclear magnetic resonance spectroscopy, mass spectrometry, dynamic light scattering, differential scanning calorimetry, and thermogravimetric analysis was verified. The results are very promising especially if such cyclic materials will be potentially used as carriers for drug delivery, either through conjugation with specific ligands or directly through the functional hydroxyl groups of the monomeric units of poly(l‐Tyr) after deprotection. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 393–404